Red Ghost Crab Ocypode Macrocera (H. Milne Edwards, 1852) Population Dynamics Changes at Bay of Bengal Coast Line in Response to Construction of Digha Marine Drive and Tajpur Port: EIA Study by Rammohan College - Chowdhury, Kaustav Dutta (International journal for research in applied science and engineering technology, 2023)
On the sand beaches of the Bay of Bengal, from Bichitrapur in Orissa to Mandermani in West Bengal, population dynamics of Ocypode macrocera (H. Milne Edwards, 1852) were investigated. The crabs are found across the coastal areas that face the sea. Bichitrapur, Talsari, Udaipur, New Digha, Mohana, Shankarpur, Tajpur, and Mandermoni were the principal study locations. The infra-littoral sand flats zone is where the Red Ghost Crabs live. The development of the particular stretch of beach and the prevalence of crab burrows are related. Crab activity occurs both during the day and at night. One to three openings towards the sea can be found in each crab burrow. EIA (Environmental Impact Assessment) is an essential study required before onset of any project or for any ongoing project. This EIA study was conducted in 2017, prior to the start of "Marine drive & Tajpur port" construction, and in 2020, following completion of "Marine drive& Tajpur port" by Rammohan College. At the construction areas, it was discovered that the Red Ghost Crab population had substantially decreased. Additionally altered is the burrow distribution pattern. An essential ecological stabilizer of Sea beach is the red ghost crab. Additionally, it was discovered that the sea beach began to erode where the crabs were completely gone.